The learning curve in post-operative hearing results in vestibular schwannoma surgery - Kanzaki, Jin; Inoue, Yasuhiro; Ogawa, Kaoru (Auris Nasus Larynx, 2001)
Purpose: We chronologically investigated whether the hearing preservation (HP) rate improved or not in vestibular schwannoma (VS) surgery. Subjects and methods: HP surgery has been attempted in 127 VS patients with pre-operative class A and B hearing from 1976 to 1999. The HP rate was chronologically compared with hearing level and tumor size. Results: The preservation rate of pre-operative class A hearing which was preserved post-operatively as class A has recently been increasing especially in patients with an intracanalicular (IC) tumor. This rate was improved to 67% from 1995, although this was 33% from 1989 to 1994. However, the preservation rate of pre-operative class B in patients with an IC tumor and that of pre-operative class A hearing which was preserved as class A in patients with a larger tumor extending into the posterior fossa, have not improved over the last 10 years. Conclusion: These results indicate that the improvement of the HP rate is mainly due to the increased number of patients with an IC tumor with class A pre-operative hearing. In patients with a tumor of 4–20 mm in size, especially in those showing pre-operative class B hearing, there may be histologically some limitations such as gliosis in the cochlear nerve in the preservation rate of good quality (class A or B) of hearing.